Management of Teacher Working Group in Elementary School - Hamsani (Jurnal Pendidikan Islam Al-Affan, 2021)
This article aims to see the management functions of the implementation of the Teacher Working Group (TWG) program. Where in the implementation of these activities the management function is indispensable in the implementation of the activity itself. Researchers are motivated to conduct research by describing all planning, organizing, implementation and control activities in the TWG in cluster 5 of Palangka Raya city in Jekan Raya Subdistrict. With this TWG, educators can improve professionalism by discussing, the practice of making Lesson Plan, the preparation of annual programs (Prota), semester programs (Promes), analysis of lesson materials, teaching unit programs, learning methods, evaluation tools, teaching materials, the creation and utilization of teaching media can also be reviewed in this forum. This study used qualitative approach with descriptive design, to illustrate the management of TWG in Palangka Raya. The research object is Teacher Working Group (TWG) cluster 5 in Palangka Raya City. The research subjects were head of TWG Cluster 5, and Madrasah Supervisor. Study found planning of Teacher Working Group (TWG) cluster 5 based on Work programs which includes: General work program, principal program and meeting time and schedule which aims to optimize the activities, so that the activities carried out can run smoothly in realizing the professionalism of an educator. Organizing conducted by the TWG cluster 5 conducted at each activity in accordance with the area of expertise of each member. Implementation contained in the TWG cluster 5 is a meeting of activities that they do once a month to discuss the issue of learning in schools. Controlling is carried out by the chairman of the TWG cluster 5 is by identifying problems in the field, then formulating the solution of each problem that exists, so that each member can do the work according to the plan. Keywords: Teacher Working Group, Management of Teacher, Management Education